Evaluasi Implementasi SPIP Berdasarkan Kerangka Pengendalian Internal COSO dalam Perencanaan Anggaran di BAPPEDA Kabupaten Buleleng - Pratiwi, Putu Rani; Gst. Ayu Ketut Rencana Sari Dewi, S.E., M.Si.; Dr. Made Aristia Prayudi, S.A., M.Sc., Ak. (Vokasi : Jurnal Riset Akuntansi, 2025)
Abstract This study aims to evaluate the implementation of the Government Internal Control System (SPIP) based on the COSO internal control framework in budget planning at BAPPEDA (Regional Development Planning Agency) of Buleleng Regency. This research employs a qualitative approach with data collection techniques including interviews, observations, and documentation to obtain an in-depth understanding of SPIP implementation in the budget planning process. The findings indicate that the implementation of SPIP at BAPPEDA Buleleng has referred to the five main components of the COSO framework, namely control environment, risk assessment, control activities, information and communication, and monitoring. However, several challenges that hinder the effectiveness of SPIP were identified, including limited human resources in terms of quantity and competence, suboptimal information systems in supporting data-driven decision-making processes, and misalignment of planning documents that result in overlapping development policies. By understanding these obstacles, this study provides strategic recommendations to strengthen the internal control system. It is expected that strengthening SPIP will contribute to the realization of more effective, transparent, and accountable budget planning